치위생과 학생들의 대학생활 스트레스에 영향을 미치는 요인 - 강용주(Yong-Ju Kang); 이지영(Ji-Young Lee) (한국콘텐츠학회 논문지, 21(1), 2021)
This study was conducted to investigate the relationship between major satisfaction, depression, self esteem and life stress among college dental hygiene students. This study targeted 227 dental hygiene student in one school. Data were analyzed using descriptive analyses, t-tests, ANOVA, Pearson's correlation, and Hierarchical multiple regression with the SPSS WIN 21. program. The results of this study were as follows: The average score of major satisfaction was 3.65±.59, the score of depression was 1.74±.43, the score of self esteem was 3.59±.70, the score of life stress was 1.50±.33. Life stress was negatively related to major satisfaction and self esteem, and positively related to depression. The factors influencing the life stress of dental hygiene students were grade, economic status, major satisfaction, depression. Overall, to decrease life stress among dental hygiene student, it is necessary to develop educational method and program that can prevent and mitigate depression and can increase major satisfaction. 본 연구는 치위생과 학생들의 전공만족도, 우울감, 자아존중감이 대학생활스트레스에 미치는 영향을 파악하기 위해 실시하였다. 경남 소재 J대학에 재학 중인 치위생과 학생 227명을 대상으로 자기기입식 설문지로 설문조사하였다. 수집된 자료는 SPSS WIN 21을 이용하여 기술통계, t-test, ANOVA, 피어슨상관분석, 위계적 회귀분석을 실시하였다. 연구결과, 전공만족도 점수는 3.65±.59점, 우울감 점수는 1.74±.43점, 자아존중감 점수는 3.59±.70점, 대학생활 스트레스 점수는 1.50±.33점이었다. 대학생활 스트레스는 전공만족도, 자아존중감과는 부적상관이 있었으며, 우울감과는 정적상관이 있었다. 대학생활 스트레스에 영향을 미치는 요인은 학년, 소득, 전공만족도, 우울감이었다. 그 결과, 치위생과 학생들의 대학생활 스트레스를 최소화하기 위하여 우울을 예방하고 완화하며, 전공만족도를 높일 수 있는 교육방법과 프로그램 개발이 필요하다고 사료된다.